(untitled) (Bangladesh Journal of Medical Science, 2023)
Background: The mainstay of care for lowering maternal and perinatal mortality and morbidity is antepartum foetal surveillance. Numerous techniques are used, including fetal movements, Vibroacoustic stimulation tests, contraction stress tests, biophysical profiles of the fetus, modified biophysical profiles, non-stress testing and Doppler Umbilical artery of the fetus’s. The fetal heart reaction to internal and extrinsic stimuli is seen on electronic fetal monitoring devices. The benefit of high resolution dynamic ultrasonography and Doppler imaging is that it allows for the visualization of the fetus and its surroundings as well as the monitoring of fetal health by measuring utero-placental circulation. Patients and techniques: The cross-sectional investigation including 120 pregnant women who visited the Maternity Teaching Hospital between 26 June and 31 August 2022 and complained of decreased uterine contractions have been included. The questionnaire included sociodemographic data, obstetrical data, information on the fetal outcome and method of delivery. In accordance with the American Academy of Obstetricians and Gynecologists, cardiotopography was utilized to conduct a non-stress test, and the outcomes were categorized as reactive and non-reactive. Cardiotopography was used to perform a non-stress test, and the results were classified as reactive or non-reactive in accordance with the American Academy of Obstetricians and Gynecologists. Also, during 32 weeks or more of gestation, the inferior vena cava was not compressed by the gravid uterus during ultrasonography of the umbilical arteries, which was performed in a semi-recumbent position with a slight lateral tilt. Result: Based on NST and Doppler velocimetry of the umbilical artery, all cases were classified into two groups. The outcomes of the two tests didn’t significantly differ from one another. The rate of Cesarean section (CS) was 46.1% among women with non-reactive (abnormal) CTG, compared with 25% among women with normal CTG (p = 0.0316). Only one neonate (1.3%) died among women with normal CTG, while none of the neonates died among women with abnormal CTG. The rate of CS among women with abnormal ultrasonography was 80% compared to women (11%) with normal ultrasonography. Furthermore, one neonate (2.1%) in the group of abnormal doppler, compared with 0% in the normal group. Conclusion: NST and umbilical artery Doppler of are sensitive and specific tests with strong positive prognostic value to suggest a poor prognosis for the newborn. Doppler velocimetry of umbilical artery is more important than a non-stress test because it lowers the likelihood of a CS birth in non-reactive non-stress test situations without increasing the risk of perinatal morbidity and mortality. Bangladesh Journal of Medical Science Vol.22 (Special Issue) 2023 p.10-17